2012
DOI: 10.1063/1.3703612
|View full text |Cite
|
Sign up to set email alerts
|

Current transport mechanism of heterojunction diodes based on the reduced graphene oxide-based polymer composite and n-type Si

Abstract: Millimeterwave Schottky diode on grapene monolayer via asymmetric metal contacts J. Appl. Phys. 112, 084302 (2012) Electrical and microstructural analyses of 200MeV Ag14+ ion irradiated Ni/GaN Schottky barrier diode Appl. Phys. Lett. 101, 153508 (2012) Theory of the suspended graphene varactor Appl. Phys. Lett. 101, 153102 (2012) Localized surface plasmon-enhanced ultraviolet electroluminescence from n-ZnO/i-ZnO/p-GaN heterojunction light-emitting diodes via optimizing the thickness of MgO spacer layer Appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…PEDOT:PSS represents the next-generation of electrodes because of its high transparency in the visible range, its solution processability, its high work function, and its significant mechanical flexibility. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] With the widespread use of PEDOT:PSS, a number of studies are attempting to determine and improve its properties. A common method that is used to improve the properties of PEDOT:PSS is a chemical treatment that involves the addition of co-solvents, which results in considerable improvement to the polymer's conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT:PSS represents the next-generation of electrodes because of its high transparency in the visible range, its solution processability, its high work function, and its significant mechanical flexibility. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] With the widespread use of PEDOT:PSS, a number of studies are attempting to determine and improve its properties. A common method that is used to improve the properties of PEDOT:PSS is a chemical treatment that involves the addition of co-solvents, which results in considerable improvement to the polymer's conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one can achieve tunable optoelectronic properties of GO by modifying its oxygenated functional groups either chemically or thermally [20,23]. Numerous studies have been reported prospecting their applications in photo detectors [24], thin film transistors [25], transparent conducting electrodes [26] and supercapacitors [27]. Recently, several research groups reported remarkable nonlinear optical properties of graphene and GO, such as nonlinear absorption and broadband optical limiting, two-photon absorption (TPA) [28,29], saturable absorption [30] and excited state absorption (ESA) [31], which make GO an ideal material for photonic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] The incorporation of inorganic nanocrystals in the organic matrix allows an inexpensively solution processing of the hybrid organic-inorganic device. 16,[24][25][26][27][28][29][30] These technologies are aimed at combining the advantages of different material systems to provide better efficiency, more cost efficient manufacturing, or both. In addition, the effect of charge trapping on the electrical properties of the organicon-inorganic diode has yet to be elucidated in detail.…”
mentioning
confidence: 99%